Fine's Fragmentalist Interpretation of Special Relativity. (19th May 2016) - Hofweber, Thomas; Lange, Marc
Abstract: In "Tense and Reality", Kit Fine (2005 ) proposed a novel way to think about realism about tense in the metaphysics of time. In particular, he explored two non‐standard forms of realism about tense ("external relativism" and "fragmentalism"), arguing that they are to be preferred over standard forms of realism. In the process of defending his own preferred view, fragmentalism, he proposed a fragmentalist interpretation of the special theory of relativity (STR), which will be our focus in this paper. After presenting Fine's position, we will raise a problem for his fragmentalist interpretation of STR. We will argue that Fine's view is in tension with the proper explanation of why various facts (such as the Lorentz transformations) obtain. We will then consider whether similar considerations also speak against fragmentalism in domains other than STR, notably fragmentalism about tense.